Understanding cultural clusters: An ethnographic perspective. (13th September 2022) - Wiessner, Polly
Abstract: The cultural evolutionary approach to the dynamics of cumulative culture is insufficient for understanding how culture affects heritability estimates; it ignores the agency of individuals and internal complexity of social groups that drive cultural evolution. Both environmental and social selection need consideration. The WEIRD (western, educated, industrialized, rich, and democratic) problem has never plagued anthropology: A wealth of ethnography is available for the problem at hand.